THE EFFECT OF SKILL AND KNOWLEDGE ON THE PERFORMANCE EMPLOYEE AT THE PT. VIRAJAYA PUTRA TAMBANG - Erwan Sumanto; Yulizar Baharuddin; Zamhir Basem (Jurnal Riset Manajemen Indonesia, 2021)
Research to determine the effect of skill and knowledge on the performance employee with simulthan and partial at the PT. Virajaya Putra Tambang. Types and sources of data used in this study are primary data and secondary data, while data collection techniques used in this study were questionnaires, file research, observation and interviews. The population in this study were all employee at the PT. Virajaya Putra Tambang in 2019, amounting to 94 employee and al employees were sampled so that the sampling technique in this research used a saturated census technique. Data analysis was performed using multiple linear regression models.Based on the simulthan test results, the variable of skill and knowledge have a significant effect with together on the performance employee at the PT. Virajaya Putra Tambang, while based on the partial test results, the variable of skill and knowledge have a significant effect with individual on the performance employee at the PT. Virajaya Putra Tambang. The closeness of the relationship that occurs between the atractiveness of skill and knowledge on the performance employee at the PT. Virajaya Putra Tambang is strong with a correlation coefficient R of 79,6%. Contribution of skill and knowledge on the performance employee variables is equual to 63.3% while the remaining 36,7% is influenced by other variables not examined in this study.